Effectiveness of Using the Moodle Platform in Developing Students’ Speaking Skills - EKA PRATIWI YUNIANTI (Teaching English and Language Learning English Journal, 2025)
The growing integration of digital tools in language instruction has created new opportunities for improving speaking competence among EFL learners. This study aims to explore the effectiveness of Moodle, a widely used Learning Management System (LMS), in enhancing students’ speaking skills in an English course designed for non-English majors. The participants were 30 students from the Accounting Study Program at University of Aisyah Pringsewu, enrolled during the 2024/2025 academic year. A one-group pre-test and post-test design was employed to assess changes in performance following an eight-week Moodle-based intervention. Speaking tasks were delivered through Moodle features, including voice recordings, discussion forums, and peer feedback. Assessments were conducted using standard TOEFL/IELTS-based speaking rubrics. Descriptive statistical analysis revealed a significant improvement in speaking scores, with the average rising from 57.63 (pre-test) to 79.73 (post-test). The normality of the data was confirmed using the Shapiro-Wilk test, and a paired samples t-test yielded a statistically significant difference (p < 0.05), supporting the effectiveness of the intervention. The structured, asynchronous learning environment provided by Moodle enabled students to practice consistently, build confidence, and reduce performance anxiety. Furthermore, the integration of interactive and reflective speaking activities promoted greater learner autonomy. These findings suggest that Moodle can be a valuable platform for fostering speaking development in higher education, particularly for students outside language-related majors. It also highlights the potential of LMS-based instruction to support communicative competence in EFL contexts. Keywords : Moodle, speaking skills, digital learning, EFL students